2006
DOI: 10.1021/ct050196z
|View full text |Cite
|
Sign up to set email alerts
|

Improved Efficiency of Replica Exchange Simulations through Use of a Hybrid Explicit/Implicit Solvation Model

Abstract: The use of parallel tempering or replica exchange molecular dynamics (REMD) simulations has facilitated the exploration of free energy landscapes for complex molecular systems, but application to large systems is hampered by the scaling of the number of required replicas with increasing system size. Use of continuum solvent models reduces system size and replica requirements, but these have been shown to provide poor results in many cases, including overstabilization of ion pairs and secondary structure bias. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
185
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 141 publications
(192 citation statements)
references
References 76 publications
7
185
0
Order By: Relevance
“…The average secondary structure propensities and local conformational preferences of all residues in each simulation are given in Table 1. The overall agreement between independent simulations for each solvent model (as indicated by the small error values) shows that good convergence was achieved for all simulations; excellent convergence for these ensembles has been reported previously 21 .…”
Section: Secondary Structure and Conformational Analysissupporting
confidence: 80%
See 1 more Smart Citation
“…The average secondary structure propensities and local conformational preferences of all residues in each simulation are given in Table 1. The overall agreement between independent simulations for each solvent model (as indicated by the small error values) shows that good convergence was achieved for all simulations; excellent convergence for these ensembles has been reported previously 21 .…”
Section: Secondary Structure and Conformational Analysissupporting
confidence: 80%
“…The distribution of temperatures was chosen to ensure good overlap of potential energy between replicas and to achieve an exchange acceptance ratio of 0.20. The TIP3P REMD simulations involved 40 replicas at temperatures ranging from 266.9 to 571.2 K. Since the GB REMD simulations had far fewer degrees of freedom, only 8 replicas were required at temperatures ranging from 269.5 to 570.9 K. All data analysis was performed on REMD structure ensembles at 300.0 K. The high degree of convergence of these ensembles has been demonstrated in a previously published study 21 .…”
Section: Remd Simulation Detailsmentioning
confidence: 99%
“…If, for example, PP II is indeed stabilized by specific interactions with explicit water as recently suggested 57,66-68 , such stabilization is not possible with implicit solvents, and thus structural preference may change. In fact, we recently reported that GB solvation models increase α-helical propensity 69 . Different approaches in force field development might be needed to account for these effects, and force fields should likely be tested with the particular characteristics (and perhaps idiosyncrasies) of these models in mind.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the improved glycine parametrization was important in our recent simulations of HIV-1 protease 70 , where glycine rich "flaps" play an essential role in protease dynamics. Another study 69 reported a hybrid replica exchange method, where ff99SB was used to test the methodology based on conformational sampling of polyalanine peptides of varying lengths. Our recent simulations 71 of fragments of the villin headpiece with ff99SB also achieved good agreement with experimental trends 72 in calculated J-coupling constants and helical propensities.…”
Section: Discussionmentioning
confidence: 99%
“…The application of the REMD method to larger protein-glycan systems requires a large number of replicas. There have been several attempts to reduce the number of replicas, such as using REMD with a hybrid explicit/implicit solvation model (Okur et al 2006), solute tempering (Liu et al 2005), and REMD coupled to a high-temperature structure reservoir (Okur et al 2007). Such methods and further methodological developments could lead to accurate free-energy calculations of protein-glycan binding, and help explore the relationship between the flexibility of glycans and their specific recognition.…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%